The impact assessment of the EU pre-accession funds on agriculture and food companies: The Croatian case - Kukoč, Marin; Škrinjarić, Bruno; Juračak, Josip (Spanish Journal of Agricultural Research, 2021)
Aim of study: This paper evaluates the effect of pre-accession EU grants on beneficiaries in the agri-food sector using a quasi-experimental approach on the case of Croatia. An insight into the available literature reveals a lack of rigorous research and evaluation of the results of using these funds in Croatia as well as in other beneficiary countries.Area of study: Republic of Croatia, Europe (2006–2017).Material and methods: Two datasets were used: (1) financial and structural data on the population of Croatian enterprises for the 2003–2017 period, and (2) data on SAPARD and IPARD grants in the 2007–2016 period. Data were analyzed using counterfactual impact analysis, i.e., a combination of difference-in-difference approach and propensity score matching.Main results: The grants showed to have a positive effect on firm survival, as well as positive effects on obtaining bank loans and increasing turnover, value added, employment, and total factor productivity. Heterogeneous treatment effects show that the grants resulted in the greatest additionality for micro-sized firms located in Central Croatia. Cost-benefit analysis estimates an increase in the value added, which outweighs scheme-induced costs by 120% in the short run and 90% in the mid run.Research highlights: Pre-accession programs in Croatia had a positive impact on the beneficiaries’ growth and business performance indicators in both short and mid term. This paper also promotes the application of similar research in other EU candidate countries where the same or similar funds are implemented.